Changes in miRNA expression in patients with peripheral arterial vascular disease during moderate- and vigorous-intensity physical activity - Johanna Sieland; Daniel Niederer; Tobias Engeroff; Lutz Vogt; Christian Troidl; Thomas Schmitz-Rixen; Winfried Banzer; Kerstin Troidl (European Journal of Applied Physiology, 2022)
Background Walking is the preferred therapy for peripheral arterial disease in early stage. An effect of walking exercise is the increase of blood flow and fluid shear stress, leading, triggered by arteriogenesis, to the formation of collateral blood vessels. Circulating micro-RNA may act as an important information transmitter in this process. We investigated the acute effects of a single bout of 1) aerobic walking with moderate intensity; and 2) anaerobic walking with vigorous intensity on miRNA parameters related to vascular collateral formation. Methods Ten (10) patients with peripheral arterial disease with claudication (age 72 ± 7 years) participated in this two-armed, randomized-balanced cross-over study. The intervention arms were single bouts of supervised walking training at (1) vigorous intensity on a treadmill up to volitional exhaustion and (2) moderate intensity with individual selected speed for a duration of 20 min. One week of washout was maintained between the arms. During each intervention, heart rate was continuously monitored. Acute effects on circulating miRNAs and lactate concentration were determined using pre- and post-intervention measurement comparisons. Results Vigorous-intensity walking resulted in a higher heart rate (125 ± 21 bpm) than the moderate-intensity intervention (88 ± 9 bpm) ( p < 0.05). Lactate concentration was increased after vigorous-intensity walking ( p = 0.005; 3.3 ± 1.2 mmol/l), but not after moderate exercising ( p > 0.05; 1.7 ± 0.6 mmol/l). The circulating levels of miR-142-5p and miR-424-5p were up-regulated after moderate-intensity ( p < 0.05), but not after vigorous-intensity training ( p > 0.05). Conclusion Moderate-intensity walking seems to be more feasible than vigorous exercises to induce changes of blood flow and endurance training-related miRNAs in patients with peripheral arterial disease. Our data thus indicates that effect mechanisms might follow an optimal rather than a maximal dose response relation. Steady state walking without the necessity to reach exhaustion seems to be better suited as stimulus.

Effects of single bouts of different endurance exercises with different intensities on microRNA biomarkers with and without blood flow restriction: a three-arm, randomized crossover trial - Johanna Sieland; Daniel Niederer; Tobias Engeroff; Lutz Vogt; Christian Troidl; Thomas Schmitz-Rixen; Winfried Banzer; Kerstin Troidl (European Journal of Applied Physiology, 2021)
Purpose Physical activity is associated with altered levels of circulating microRNAs (ci-miRNAs). Changes in miRNA expression have great potential to modulate biological pathways of skeletal muscle hypertrophy and metabolism. This study was designed to determine whether the profile of ci-miRNAs is altered after different approaches of endurance exercise. Methods Eighteen healthy volunteers (aged 24 ± 3 years) participated this three-arm, randomized-balanced crossover study. Each arm was a single bout of treadmill-based acute endurance exercise at (1) 100% of the individual anaerobic threshold (IANS), (2) at 80% of the IANS and (3) at 80% of the IANS with blood flow restriction (BFR). Load-associated outcomes (fatigue, feeling, heart rate, and exhaustion) as well as acute effects (circulating miRNA patterns and lactate) were determined. Results All training interventions increased the lactate concentration (LC) and heart rate (HR) ( p < 0.001). The high-intensity intervention (HI) resulted in a higher LC than both lower intensity protocols ( p < 0.001). The low-intensity blood flow restriction (LI-BFR) protocol led to a higher HR and higher LC than the low-intensity (LI) protocol without BFR ( p = 0.037 and p = 0.003). The level of miR-142-5p and miR-197-3p were up-regulated in both interventions without BFR ( p < 0.05). After LI exercise, the expression of miR-342-3p was up-regulated ( p = 0.038). In LI-BFR, the level of miR-342-3p and miR-424-5p was confirmed to be up-regulated ( p < 0.05). Three miRNAs and LC show a significant negative correlation (miR-99a-5p, p = 0.011, r = − 0.343/miR-199a-3p, p = 0.045, r = − 0.274/miR-125b-5p, p = 0.026, r = − 0.302). Two partial correlations (intervention partialized) showed a systematic impact of the type of exercise (LI-BFR vs. HI) (miR-99a-59: r = − 0.280/miR-199a-3p: r = − 0.293). Conclusion MiRNA expression patterns differ according to type of activity. We concluded that not only the intensity of the exercise (LC) is decisive for the release of circulating miRNAs—as essential is the type of training and the oxygen supply.

Achieving the ideal properties for vascular bypass grafts using a tissue engineered approach: a review - Sandip Sarkar; Thomas Schmitz-Rixen; George Hamilton; Alexander M. Seifalian (Medical & Biological Engineering & Computing, 2007)